Quality Standardization of Coccinia indica Fruit - Ajay, S.S.; Bhaskar, V.H.; Teotia, Deepak (Asian Journal of Chemistry, 2010)
Coccinia indica fruit were collected from the market of Ghaziabad, India and identified and standardized as per WHO guidelines.